Use of antifungals in the treatment of vulvovaginal candidiasis: an integrative review - Moreira, Kellyane Folha Gois; Feitosa, Carla Danielle Araújo; Magalhães, Camila Fortes Castelo Branco; Nascimento, Matheus Oliveira do; Carvalho, André Luis Menezes; Silva-Júnior, Fernando Lopes e (Revista de Enfermagem da UFPI, 2023)
Objective: To identify scientific evidence available in the literature and analyze the action of antifungal drugs used for the treatment of vulvovaginal candidiasis. Methods: Integrative literature review conducted in the databases Medline/PubMed, Embase, Web of Science, Cochrane Library, CINAHL, SCOPUS and VHL; with the descriptors "woman", "antifungal agents"; "vulvovaginal candidiasis". Results: Ten scientific articles published between 1983 and 2020 were obtained. Of these, four were developed in Iran; followed by Mexico, England, Taiwan, Thailand, Denmark, and the United States. In terms of methodological design, most studies are clinical trials (n=8), and two are cross-sectional studies. Regarding the level of evidence, eight are level II, and only two investigations are level IV. Concerning the antifungal drugs used in the treatment, there was a predominance of clotrimazole (n=4; efficacy ranging from 42.4% to 98.3%), followed by econazole (n=2; efficacy between 39% and 89%), combined or not with another antifungal drug. Conclusion: The use of clotrimazole stands out, as it is highly effective in the treatment of vulvovaginal candidiasis. This study contributes to the advancement of knowledge and improvement of the clinical practice of nursing and other health professionals. It is expected that these results will encourage further studies and update clinical practices.